1998
DOI: 10.1159/000014035
|View full text |Cite
|
Sign up to set email alerts
|

Surface Tension, Glutathione Content and Redox Ratio of the Tracheal Aspirate Fluid of Premature Infants with IRDS

Abstract: Objective: Determination of the surface tension (ST), the total glutathione (GL) content and the ratio of oxidized glutathione (GSSG) to reduced glutathione (GSH) in the tracheal aspirate (TA) of newborn infants with IRDS. Methods: The ST of the TA was determined by monitoring the fluid level pulsated in a capillary glass tube by means of a digitalized videocomputerized picture analysis program, a technique developed in our laboratory. The concentrations of GSSG and total GL in the TA were determined enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…One previous study showed a decrease in both the GSSG concentration and in the GSSG/GSH ratio in the tracheal aspirate of newborns with RDS after surfactant treatment. 12 The primary aim of our study was to evaluate the oxidant/ antioxidant status in preterm infants with RDS via measurement of total antioxidant capacity (TAC) and total oxidant status (TOS) and to determine the effect of surfactant on oxidant/antioxidant balance. The secondary outcome was to assess the association between TAC, TOS and clinical outcomes of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…One previous study showed a decrease in both the GSSG concentration and in the GSSG/GSH ratio in the tracheal aspirate of newborns with RDS after surfactant treatment. 12 The primary aim of our study was to evaluate the oxidant/ antioxidant status in preterm infants with RDS via measurement of total antioxidant capacity (TAC) and total oxidant status (TOS) and to determine the effect of surfactant on oxidant/antioxidant balance. The secondary outcome was to assess the association between TAC, TOS and clinical outcomes of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…SOD plays a fundamental role in modulating oxygen toxicity and its induction seems related to the extent of the redox abnormality in the cell (30)(31)(32)(33). Significantly lower GPX activity, estimated at birth, in preterms receiving supplemented oxygen treatment and even more depressed in those who required mechanical ventilation could be a consequence of a selenium deficiency and, also, a possible glutathione (GSH) deficit in these groups, as has been reported by several authors (34)(35)(36)(37). This could lead to an inadequate activity of the glutathione system and therefore less regeneration of glutathione peroxidase, since GPX catalyses the reduction of hydro gen peroxide (H 2 O 2 ) and hydroperoxides originating from polyunsaturated fatty acids at the expense of reduced GSH.…”
Section: Discussionmentioning
confidence: 57%
“…Confirmed data in a previous study of 32 intubated preterm and newborn infants with respiratory distress syndrome (RDS) and admitted to a neonatal intensive care unit (NICU) showed a low total GSH level in TA when compared with 11 control children (35). The MDA level in alveolar fluid was significantly high from ventilator-associated pneumonia (VAP) (36).…”
Section: Discussionmentioning
confidence: 66%